2019
DOI: 10.3390/agronomy9080467
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes and Increased Levels of Bioactive Compounds in White Radish (Raphanus sativus L. cv. 01) Sprouts Elicited by Oligochitosan

Abstract: The effect of oligochitosan O-80 treatment on metabolic changes in white radish (Raphanus sativus L.) sprouts (WRS) was investigated for its potential to enhance bioactive compounds accumulation. The seeds were germinated in deionized water containing different concentrations of oligochitosan O-80 (0 (control), 5, 10, 20 and 40 ppm). Seven-day old sprouts were harvested for metabolome analysis using liquid chromatography-mass spectrometry (LC-MS) and high-performance liquid chromatography (HPLC) for phenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…There is much less data available in the literature on the composition of the phenolic compounds in radish sprouts [2,28,29]. It was shown that the main phenolic compounds in radish sprouts were derivatives of sinapic acid [2,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is much less data available in the literature on the composition of the phenolic compounds in radish sprouts [2,28,29]. It was shown that the main phenolic compounds in radish sprouts were derivatives of sinapic acid [2,28].…”
Section: Introductionmentioning
confidence: 99%
“…There is much less data available in the literature on the composition of the phenolic compounds in radish sprouts [2,28,29]. It was shown that the main phenolic compounds in radish sprouts were derivatives of sinapic acid [2,28]. In another study, sprouts were shown to contain quercetin, ferulic acid, caffeic acid, and p-coumaric acid as well as their derivatives [29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Li et al [160] suggested that oligochitosan induced the production of nitric oxide and hydrogen peroxide in Brassica napus L. plants, which acted as signaling molecules in the regulation of stomata closure and the expression of LEA protein gene for the protection against drought. Apart from protective effects, oligochitosan may improve the functional properties of vegetable products, as already reported in case of white radish sprouts (Raphanus sativus L.) where seed germination with oligochitosan-treated water resulted in a significant increase in the most abundant glucosinolate, e.g., glucoraphasatin [161].…”
Section: Activities and Applications Of Oligochitosanmentioning
confidence: 66%
“…Further studies should focus on the use of exogenous melatonine [46,47], elicitors (exogenous IBA, fungal elicitors, and oligochitosan), and/or precursor feeding in the overproduction of valuable metabolites in the bleeding heart [48].…”
Section: Biosynthesis Of Metabolites In Callusmentioning
confidence: 99%